A protein-centric approach for the identification of folate enzymes from the malarial parasite, Plasmodium falciparum, using OFFGEL™ solution-based isoelectric focussing and mass spectrometry - Sims Paul FG (Malaria Journal, 2010)
Abstract Background Plasmodium species are difficult to study using proteomic technology because they contain large amounts of haemoglobin-derived products (HDP), generated by parasite breakdown of host haemoglobin. HDP are known to interfere with isoelectric focussing, a cornerstone of fractionation strategies for the identification of proteins by mass spectrometry. In addition to the challenge presented by this material, as in most proteomes, there exists in this parasite a considerable dynamic range between proteins of high and low abundance. The enzymes of the folate pathway, a proven and widely used drug target, are included in the latter class. Methods This report describes a work-flow utilizing a parasite-specific extraction protocol that minimizes release of HDP into the lysate, followed by in-solution based OFFGEL™ electrophoresis at the protein level, trypsin digestion and mass spectrometric analysis. Results It is demonstrated that, by removing HDP from parasite lysates, OFFGEL™-mediated protein separation is able to deliver reduced complexity protein fractions. Importantly, proteins with similar and predictable physical properties are sharply focussed within such fractions. Conclusions By following this novel workflow, data have been obtained which allow the unequivocal experimental identification by mass spectrometry of four of the six proteins involved in folate biosynthesis and recycling.